CHOLINESTERASE INHIBITORS IN THE TREATMENT OF DEMENTIA ALZHEIMER’S - Prameidya Primaniar S (E-Jurnal Medika Udayana, 2013)
Dementia is the loss of intellectual abilities which include decreased ability to think, remember,understand, calculate, concentrate, and find the right words. The causes of dementia areAlzheimer’s, vascular dementia, alcohol. Dementia Alzheimer’s is a dementia type that iscurrently the most commonly found. Cholinesterase inhibitors are one of the therapies used totreat symptoms of cognitive decline and reduce neuropsychiatric symptoms in patient dementiaAlzheimer’s. Several studies have been conducted to demonstrate how the effects of severalclasses of cholinesterase inhibitors in the treatment of dementia Alzheimer’s. Effective dose,dosage and side effects of cholinesterase inhibitors is important to know before deciding to usecholinesterase inhibitors in the treatment of dementia Alzheimer’s.